THE EFFECT OF MANAGERIAL INTELLIGENCE ON PROJECT OUTCOMES: HOW PARTICIPATIVE AND DIRECTIVE LEADERSHIP STYLES INFLUENCE PUBLIC ENTERPRISES IN JORDAN - Al-Safadi, Malek (Ayden International Journal of Banking, Finance and Technology, 2024)
Project success (PS) is essential in project management, and various studies have explored the variables that contribute to PS. However, the impact of leaders’ managerial intelligence (MI) on PS has received limited attention, especially in the context of public corporations in Jordan. This study aimed to investigate the relationship between MI and PS and the moderating role of participative and directive leadership styles (PLS and SLS) in this relationship. A quantitative research design was employed, and data were collected using a questionnaire survey from 216 toplevel managers in public corporations in Jordan. Structural equation modeling was used to test the hypothesized model, and the results indicated that MI significantly contributed to PS. Moreover, SLS was found to moderate the relationship between MI and PS. The study's findings have practical implications for project managers in public corporations, emphasizing the importance of MI and leadership styles in achieving PS.